2004
DOI: 10.5194/hess-8-1076-2004
|View full text |Cite
|
Sign up to set email alerts
|

Snowmelt and sublimation: field experiments and modelling in the High Atlas Mountains of Morocco

Abstract: Snow in the High Atlas Mountains is a major source for freshwater renewal and for water availability in the semi-arid lowlands of southeastern Morocco. Snowfall-and snow-ablation monitoring and modelling is important for estimating potential water delivery from the mountain water towers to the forelands. This study is part of GLOWA-IMPETUS, an integrated management project dealing with scarce water resources in West Africa. The Ameskar study area is located to the south of the High Atlas Mountains, in their ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 10 publications
(16 reference statements)
5
68
0
Order By: Relevance
“…of the seasonal snowpack ablation at 3000 m a.s.l. (Schulz and de Jong, 2004). The same authors noted the wide range of sublimation rates that were observed by other groups in arid mountains, emphasizing the fact that sublimation losses can considerably reduce runoff and groundwater recharge in already dry environments.…”
Section: Introductionmentioning
confidence: 62%
“…of the seasonal snowpack ablation at 3000 m a.s.l. (Schulz and de Jong, 2004). The same authors noted the wide range of sublimation rates that were observed by other groups in arid mountains, emphasizing the fact that sublimation losses can considerably reduce runoff and groundwater recharge in already dry environments.…”
Section: Introductionmentioning
confidence: 62%
“…Fourth, in a semi-arid area, water losses via evapotranspiration for the vegetation and via sublimation for snow are important, but they are perhaps not properly taken into account by a simple conceptual model such as SRM. On the southern slopes of the High Atlas, Schulz & de Jong (2004) found, with an energy balance model, that, on average, 44% of snow ablation was attributed to sublimation, and small pinnacles that could be due to sublimation (penitentes) were observed. Finally, the mechanisms of groundwater redistribution are also unrecognizable and are difficult to model (Duclaux, 2005;Chaponnière et al, 2008).…”
Section: Model Validationmentioning
confidence: 99%
“…Snowmelt contributes to 15-50 % of the stream flow in the Tensift catchment, thus playing a significant role for irrigation (Boudhar et al, 2009). The low atmospheric humidity and typically subfreezing temperatures above 3000 m favour losses by sublimation, which can account for up to 44 % of snow ablation, while at lower altitudes melting prevails (Schulz and de Jong, 2004). The only perennial snow patch in North Africa is located below the north-facing cliffs of the Tazaghart plateau (3980 m a.s.l.…”
Section: Study Areamentioning
confidence: 99%